Improved Control Strategy of Current-Source Converter for HVDC System - Wenwen Zhang; Longlong Chen; Xiaoguang Wei; Lei Qi; Ke Ji; Chong Gao; Zhiyuan He (CSEE Journal of Power and Energy Systems)
Pulse width modulated current-source converter (PWM-CSC) has great prospects in high voltage direct current transmission system (HVDC) due to its attractive features, such as flexible control characteristics, ability to avoid commutation failure, and lower cost. However, valve voltage of the PWM-CSC is the jump value between filter capacitors line-voltage and zero voltage due to its bypass operation, resulting in high peak voltage withstand by the converter for a rated HVDC system and high voltage ripper ratio. In order to solve these issues, an improved modulation method called specific carrier frequency of SPWM is proposed. After adopting the improved modulation method, the number of the reverse blocking integrated gate commutated thyristor (RB-IGCT) in series can reduce by 31.5% under unity power factor operation and the value of the dc choke can reduce by about 78.6% compared to traditional modulation methods, improving practicability of engineering application. Moreover, active power and reactive power operating range are derived under different modulation methods and the relationship of the power factor, modulation in q-axis and DC current are studied. Finally, effectiveness of the improved modulation method and comparisons of power operating range are verified in PSCAD/EMTDC.